Local self-government powers: on content and correlation with related concepts - M. A. Sambor (Law and Safety)
The article is devoted to the study of the concepts of “competency”, “competence”, “powers”, and their correlation in the formulation of powers of local self-government bodies. The study focuses on the understanding that local self-government and local self-government bodies are a product of civil society and are called upon to regulate, promote and implement the interests of civil society, associations of citizens, in particular, on the territorial principle, as well as individuals. Since local self-government is the right of residents of certain settlements to associate, local governments must provide relevant services to the community and its residents. The provision of relevant services by local self-government bodies, which are public services by their nature, involves the exercise of their powers granted to them as a result of decentralisation of power to fulfil their functions and tasks. The exercise of powers by local self-government bodies is impossible without understanding the essence and content of powers, their correlation with the subjects of exercise – the relevant officials of local self-government bodies. Thus, understanding of the holistic doctrine of powers of local self-government bodies, their functionality and hierarchy is impossible without studying the concepts of “competency” and “competence” of a local self-government official. Based on the results of the study, the author formulates the author’s own definitions of the concepts of “competency”, “competence” and “powers” of local self-government bodies.